Customer Relationship Management and Adverse Selection: What Experiences for Microfinance a Cameroon? - Sihomnou Dzukou, Hervine Mireille; Nzongang, Joseph (Acta Universitatis Danubius. Œconomica, 2023)
This article aims to analyze the effect of Customer Relationship Management on reducing adverse selection within microfinance institutions in Cameroon. This analysis is made possible through the implementation of a questionnaire survey. Carried out on a sample of 522 microfinance clients in the cities of Douala Yaoundé and Bafoussam, the resulting descriptive statistics make it possible to measure the different variables. Data processing carried out using SPSS, which, once the variables have been estimated, facilitates the design of an econometric model using bivariate probit multiple regression. The results of the study indicate that a quality welcome and personalized support have effects on reducing adverse selection. Based on these results, we can recommend that marketing managers in EMFs rely on the future value of the customer at each stage of the customer life cycle in the customer acquisition and retention phases, in order to target the right customers, and therefore reduce adverse selection.